FENOMENA MENGAJAR GURU PADA SEKOLAH DI KOTA LANGSA - Iqbal (Jurnal Dimensi Matematika, 2020)
Abstrac Teachers have an important role in improving the quality of education of students. A good teacher must meet the guu competency standard. The teacher competencies are: (1) Pedagogic Competence; (2) Professional Competence; (3) Personality Competencies; and (4) Social Competence. The purpose of this study was to determine how the teacher phenomenon is seen from the aspects of competence and the teaching process. The method used in this research is factor analysis. The research subjects were teachers at MAS Ulumul Qur'an Langsa. In the second analysis, it was obtained KMO of 0.78 while Bartlett's test with chi-square (df = 0.00) and sig = 0.000, which means the data is still valid and reliable. Based on the second variable analysis, there are no variables that do not meet the requirements of factor analysis, so these variables can be continued further. Keyword: Phenomenon, Teaching, Teacher